The cost structure of airline manufacturing and its implications in the example of airbus Se - Hannig, Jonas Oliver (2020)
In this research paper the cost structure of aircraft manufacturing and its impact on competition will be further analysed. Furthermore, consequences for Airbus’ valuation will be derived. First, a brief overview of the development of R&D costs in air craft manufacturing will be given on the example of Airbus and Boeing among others. Second, Economies of learning, scale and scope in aircraft manufacturing will be examined. Conclusion based on the results will be given in the end.